Char derived from sewage sludge of hydrothermal carbonization and supercritical water gasification: Comparison of the properties of two chars. (15th March 2021) - Wang, Chenyu; Zhu, Wei; Fan, Xihui
Graphical abstract: Highlights: The properties of chars produced by SCWG and HTC were compared; Sewage sludge and its model compound were tested as feedstock; There are differences in pore structure and combustion behavior of chars; Different formation pathway caused the difference of two chars in properties; Char produced via SCWG need further activation to obtain superior performance. Abstract: Supercritical water gasification (SCWG) is considered a promising technology for sewage sludge (SS) treatment and utilization; however, char produced by a side reaction has become a bottleneck in SCWG. In this study, SS and its model compound (10% humic acid) were treated in an autoclave by SCWG at 400 °C for 30 min and by hydrothermal carbonization (HTC) at 250 °C for 300 min. The char yield was 15.4% in SCWG and 41.3% in HTC. The chars were characterized by scanning electron microscopy, Fourier transform infrared spectroscopy, thermogravimetric analysis, Brunauer–Emmett–Teller (BET) analysis, and elemental analysis. By comparing the properties the char produced by SCWG and the hydrochar produced by HTC, which has been considered a valuable product, the feasibility of using char as an additional product in SCWG was explored. Compared with the char produced by HTC, the char generated in SCWG exhibits a lower BET specific surface area (8.257 and 15.782 m 2 /g) and combustion activity, a higher proportion of small pores (with pore sizes of 1–2 nm), and greater thermal stability. The formation pathway of the two types of chars is related to both dehydration and aromatization; decarboxylation also occurs in char formation during SCWG. Humus was proved to be related to char formation during the SCWG of SS based on experimental results obtained with the model compound. This work provides insights needed to guide follow-up treatments or utilization of the char produced during the SCWG of SS.